Etnomatematika Pembelajaran Hidroponik di SMKN SPP Asahan - Mapilindo, Mapilindo; Zulia, Cik; Rahmayanti, Sri; Lubis, Ade Fipriani (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Agriculture is an important part of Indonesian culture. Agricultural culture tends to be abandoned by the current generation with the rapid development of the times. Ethnomathematics serves as a means of exchanging knowledge between culture and education. Learning methods that support a lot of media use. The purpose of this study was to find out how hydropinic material is taught at SMK Negeri SPP Asahan. Agricultural activities help students learn mathematics and get to know and preserve their culture. This research was conducted with a qualitative descriptive approach using observation and tests. This study investigated students' knowledge of hydroponics. Information about the history and development of hydroponics to help students understand the process.